THE ROLE OF AFFECTIVE AND COGNITIVE RESPONSE IN MEDIATING THE EFFECT OF NEW PRODUCT DESIGN ON THE BEHAVIORAL BRAND LOYALTY OF LE MINERALE DRINKING WATER - Adriana Winarti; Domi Kirana; Ida Bagus Nyoman Udayana (SIMAK, 2022)
This study aims to determine the effect of Le Minerale's new drinking water product design on consumer response and consumer loyalty. This study includes causal research, namely research that finds and describes a causal relationship between the Le Minerale retailer population. The data collection technique used the observational method by distributing questionnaires. Types and sources of data using primary data, validity and reliability are used to test the questionnaire. After the data is collected, the model test and hypothesis test are carried out. SPSS was used for data analysis. The results of this study, the new product design variable has a significant positive effect on cognitive response. New product design has a significant positive effect on affective response. Cognitive response and affective response have a positive and significant effect on behavioral brand loyalty. New product design has an effect on behavioral brand loyalty through cognitive response. New product design affects behavioral brand loyalty through affective response.